Antioxidant Activity of Extracts from Bambusa vulgaris and Gigantochloa apus Kurz Bamboo Shoots - Soesanto, Edy (Pakistan Journal of Nutrition, 2016)
Bamboo shoots are easy to find in Indonesia and have been as a food ingredient since antiquity. In addition, bamboo shoots contain compounds that can reduce blood cholesterol. Thus, extracts from bamboo shoots could be used as an alternative treatment for hyperlipidemia. The aim of this study was to determine the amount flavonoids, polyphenols, vitamin E and the antioxidant activity of bamboo shoots. Bambusa vulgaris and Gigantochloa apus kurz Bamboo shoots aged 1-2 weeks and 3-4 weeks, were used. Bamboo shoots were oven dried (80°C) or freeze-dried; then, compounds were extracted using 90% ethanol. The chemical compounds were analyzed using the SNI 01-2891-1992 method for the proximate test. Quantification of antioxidant compounds and antioxidant activity were analyzed using the DPPH method. The results of the proximate analysis test, the sample of chemical compounds and antioxidant activity in this study showed that, after oven-drying, the greatest shrinkage occurred in bamboo shoots aged 1-2 weeks (69.94%) and the largest shrinkage was with freeze-dried Gigantochloa apus kurz bamboo shoots aged 1-2 weeks (77.87%). Extracts of 1-2 week-old Gigantochloa apus kurz bamboo shoots (freeze-dried) had the highest protein content (0.41%). The highest fat content was in the extract from 1-2 week-old Bambusa vulgaris bamboo shoots (oven-dried; 0.63%). The carbohydrate level from extracts of 1-2 week-old Gigantochloa apus kurz bamboo shoots (freeze-dried) was 30.23%. The crude fiber content of the extract from 3-4 week-old Bambusa vulgaris bamboo shoots (oven-dried) was 4.12 g. Three to four week-old Gigantochloa apus kurz bamboo shoots (freeze-dried) had the lowest water content (3.73%). The largest ash content was in the extract from 3-4 week-old Bambusa vulgaris bamboo shoots (freeze dried; 0.98 grams). The highest content of vitamin E was in extracts from 1-2 week-old Gigantochloa apus kurz bamboo shoots (freeze-dried; 0.4358%). The total flavonoid content was highest in extracts from 1-2 week-old Gigantochloa apus kurz bamboo shoots (freeze dried; 0.03982%). The phenol content was the highest in extracts from 1-2 week-old Gigantochloa apus kurz bamboo shoots (freeze-dried; 3.506%). Extracts from 1-2 week-old Gigantochloa apus kurz bamboo shoots (freeze-dried) had the highest antioxidant activity (IC50: 22 388 μg/L) compared to other bamboo shoots.